A Primer on Human Brain Organoids for the Neurosurgeon. Issue 4 (18th May 2020) - Blue, Rachel; Miranda, Stephen P; Gu, Ben Jiahe; Chen, H Isaac
Abstract: Human brain organoids emerged in 2013 as a technology that, unlike prior in Vitro neural models, recapitulates brain development with a high degree of spatial and temporal fidelity. As the platform matured with more accurate reproduction of cerebral architecture, brain organoids became increasingly valuable for studying both normal cortical neurogenesis and a variety of congenital human brain disorders. While the majority of research utilizing human brain organoids has been in the realm of basic science, clinical applications are forthcoming. These present and future translational efforts have the potential to make a considerable impact on the field of neurosurgery. For example, glioma organoids are already being used to study tumor biology and drug responses, and adaptation for the investigation of other neurosurgery-relevant diseases is underway. Moreover, organoids are being explored as a structured neural substrate for repairing brain circuitry. Thus, we believe it is important for our field to be aware and have an accurate understanding of this emerging technology. In this review, we describe the key characteristics of human brain organoids, review their relevant translational applications, and discuss the ethical implications of their use through a neurosurgical lens.